Elucidation of Complex Nature of PEG Induced Drought-Stress Response in Rice Root Using Comparative Proteomics Approach - Agrawal, Lalit; Gupta, Swati; Mishra, Shashank K.; Pandey, Garima; Kumar, Susheel; Chauhan, Puneet S.; Chakrabarty, Debasis; Nautiyal, Chandra S. (Frontiers in Plant Science, 2016)
Along with many adaptive strategies, dynamic changes in protein abundance seem to be the common strategy to cope up with abiotic stresses which can be best explored through proteomics. Understanding of drought response is the key to decipher regulatory mechanism of better adaptation. Rice (Oryza sativa L.) proteome represents a phenomenal source of proteins that govern traits of agronomic importance, such as drought tolerance. In this study, a comparison of root cytoplasmic proteome was done for a drought tolerant rice (Heena) cultivar in PEG induced drought conditions. A total of 510 protein spots were observed by PDQuest analysis and 125 differentially regulated spots were subjected for MALDI-TOF MS-MS analysis out of which 102 protein spots identified which further led to identification of 78 proteins with a significant score. These 78 differentially expressed proteins appeared to be involved in different biological pathways. The largest percentage of identified proteins was involved in bioenergy and metabolism (29%) and mainly consists of malate dehydrogenase, succinyl-CoA, putative acetyl-CoA synthetase and pyruvate dehydrogenase etc. This was followed by proteins related to cell defense and rescue (22%) such as monodehydroascorbate reductase and stress-induced protein sti1, then by protein biogenesis and storage class (21%) e.g. putative thiamine biosynthesis protein, putative beta-alanine synthase and cysteine synthase. Further, cell signaling (9%) proteins like actin and prolyl endopeptidase and proteins with miscellaneous function (19%) like Sgt1 and some hypothetical protein were also represented a large contribution towards drought regulatory mechanism in rice. We propose that protein biogenesis, cell defense and superior homeostasis may render better drought-adaptation. These findings might expedite the functional determination of the drought-responsive proteins and their prioritisation as potential molecular targets for perfect adaptation.